2015
DOI: 10.1186/1471-2415-15-8
|View full text |Cite
|
Sign up to set email alerts
|

Vector analysis of low to moderate astigmatism with small incision lenticule extraction (SMILE): results of a 1-year follow-up

Abstract: BackgroundTo evaluate the refractive outcomes for the correction of low to moderate astigmatism up to 1 year following small incision lenticule extraction (SMILE) surgery.MethodsThis retrospective study enrolled 98 eyes from 98 patients who underwent SMILE surgery for the correction of myopia and astigmatism. Only right eyes were included in this study to avoid the bias of orientation errors. The vector method was used to analyze the outcomes of astigmatism at 1 month, 6 months and 12 months after the procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
38
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 34 publications
14
38
1
Order By: Relevance
“…Ivarsen and Hjortdal reported that undercorrection of astigmatism increased with attempted treatment following SMILE16. Undercorrection of astigmatic error has been reported in previous studies comparing SMILE to other corneal refractive surgeries8171819. The CI was very close to 1.0 for SMILE in our cohort, representing accurate astigmatic correction.…”
Section: Discussionsupporting
confidence: 83%
“…Ivarsen and Hjortdal reported that undercorrection of astigmatism increased with attempted treatment following SMILE16. Undercorrection of astigmatic error has been reported in previous studies comparing SMILE to other corneal refractive surgeries8171819. The CI was very close to 1.0 for SMILE in our cohort, representing accurate astigmatic correction.…”
Section: Discussionsupporting
confidence: 83%
“…For low to moderate astigmatism, a previous study revealed that SMILE was an effective, safe, and stable procedure, despite having a tendency for slight undercorrection. 23 High astigmatism was considerably undercorrected after both surgical procedures. The unmodified nomogram might be one of the potential factors and could result in undercorrection.…”
Section: Discussionmentioning
confidence: 98%
“…Pedersen et al have shown significant undercorrection of cylinder with SMILE over time 20. This was mainly attributed to non-compensation of errors of cyclotorsion and non-application of nomograms during the procedure 12. However, excellent results for astigmatism treatment were observed with ReLEx SMILE, which were far better compared to the published literature on SMILE.…”
Section: Discussionmentioning
confidence: 99%
“…Data from various studies suggest that this modality is a safe and effective method to correct varying degrees of myopia, with the advantages of minimum postoperative discomfort and restrictions, less dry eye, and probably better biomechanics compared to LASIK 9,10. Studies comparing the results of astigmatism correction with ReLEx SMILE and LASIK, however, showed better outcomes with LASIK, most likely due to non-availability of iris registration and eye tracker in the current version of the femtosecond laser used for the ReLEx SMILE procedure 11,12. However, similar comparison studies have not been reported between T-ICL and ReLEx SMILE.…”
Section: Introductionmentioning
confidence: 99%